Engaging Students’ Experiences and Practices through Computer-Mediated Communication in Learning Grammar - Atik Rokhayani; Dwi Rukmini; Rudi Hartono; Dwi Anggani Linggar Bharati (International Conference on Science, Education, and Technology, 2021)
The development of technology impacts English education in numerous ways. A computer is used by teachers and students to enhance learning in an English classroom setting. The pandemic learning process enabled students to communicate more via Computer Mediated Communication (CMC). Students may connect with others all across the globe via the use of CMC. It serves as a means of communication between people. The benefits of CMC are a significant element in the success of the EFL class. The purposes of this study were to explore the EFL university students’ experience and practices through CMC in Grammar learning. This study applied a qualitative approach. The findings of the study revealed that CMC through Human-to-Human fostered a more engaging classroom experience and offered the university students with the opportunity to actively communicate with their lecturers and peers. The students also showed the positive attitudes and could ease the learning experience on the use of low technologies in learning Grammar. The present study recommends engaging EFL students’ experiences and practices through learning tools as low technologies.